Persepsi Masyarakat terhadap Kinerja Pendamping Desa dalam Pemberdayaan Masyarakat di Bidang Pertanian (Studi di Kecamatan Sungai Pagu Kabupaten Solok Selatan) - Fadila Wahyuni; Dasman Lanin (PUBLICNESS: Journal of Public Administration studies, 2022)
This study sought to ascertain how the Sungai Pagu District, South Solok Regency community felt about the performance of the village facilitators in terms of community empowerment in agriculture. This study is a study using a quantitative-descriptive approach, quantitative data collected using a Likert scale questionnaire that has been tested for validity and reliability. In this study using descriptive statistical techniques using percentage calculations as a data analysis technique. The research location is in Sungai Pagu District, South Solok Regency with 99 respondents. According to the study's findings, the perception of the people of Sungai Pagu District, South Solok Regency on the performance of Village Facilitators in community empowerment in agriculture can be categorized as high, namely 81.0725%.